On the infrared behavior of Landau Gauge Yang-Mills theory with a fundamentally charged scalar field - Fister, Leonard; Alkofer, Reinhard; Schwenzer, Kai (Physics letters, 2010)
Recently it has been shown that infrared singularities of Landau gauge QCD can confine static quarks via a linearly rising potential. We show that the same mechanism can also provide a confining interaction between charged scalar fields in the fundamental representation. This confirms that within this scenario static confinement is a universal property of the gauge sector even though it is formally represented in the functional equations of the matter sector. The simplifications compared to the fermionic case make the scalar system an ideal laboratory for a detailed analysis of the confinement mechanism in numerical studies of the functional equations as well as in gauge-fixed lattice simulations.
Gesehen am 09.05.2023